1991
DOI: 10.2527/1991.6993689x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dietary tryptophan and behavioral type on behavior, plasma cortisol, and brain metabolites of young pigs1

Abstract: The behavioral reactivity in an "open-field" test and plasma cortisol levels were studied in 72 pigs from 12 litters fed for 3 wk one of three diets with different levels of tryptophan: deficient (.14%), adequate (.23%), or excess (.32%). "Open-field" tests were performed three times: 5 d (day W + 5), 23 d (day W + 23) and 45 d (day W + 45) after weaning. The exploration time and the number of grunts provided an adequate measure of the individual emotional reactivity at day W + 5. Significant correlations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 0 publications
0
24
2
Order By: Relevance
“…Indeed, in rats, it has been shown that vitamin B 6 supplements can stimulate serotonin synthesis in the brain (Hartvig et al 1995), especially following concomitant supplementation with vitamin B 6 and tryptophan (Lee et al 1988). In pigs, a modulation of dietary tryptophan has been shown on brain serotonin (Meunier-Salau¨n et al 1991). Nevertheless, if this was also the case in the present experiment, it had no impact on animal behaviour before slaughter.…”
Section: Behaviourcontrasting
confidence: 51%
“…Indeed, in rats, it has been shown that vitamin B 6 supplements can stimulate serotonin synthesis in the brain (Hartvig et al 1995), especially following concomitant supplementation with vitamin B 6 and tryptophan (Lee et al 1988). In pigs, a modulation of dietary tryptophan has been shown on brain serotonin (Meunier-Salau¨n et al 1991). Nevertheless, if this was also the case in the present experiment, it had no impact on animal behaviour before slaughter.…”
Section: Behaviourcontrasting
confidence: 51%
“…In pigs, the level of tryptophan supply clearly impact on serotonin production in the brain: large excess of tryptophan increased brain serotonin concentration (Adeola and Ball, 1992) whereas tryptophan deficiency impaired serotonin production in the brain (Henry et al, 1996). In another way, Meunier-Salaun et al (1991) found lower tryptophan in plasma and brain of emotional piglets compared to non emotional piglets. Moreover, the ratio of 5-hydroxyindoleacetic acid (5-HIAA)/5-HT used as an indicator of serotoninergic activity was higher in the posterior brain of emotional piglets suggesting an increased 5-HT turnover and difference in tryptophan metabolism in the brain may be suspected.…”
Section: Tryptophan and The Control Of Stress Responsementioning
confidence: 94%
“…In horses large tryptophan supply has been also proposed for its sedative effect (Grimmett and Sillence, 2005). In pigs tryptophan effects on stress response and sensitivity has been confirmed in the cases of deficiency or after the administration of large pharmacological doses of this amino acid (Koopmans et al, 2005;Guzik et al, 2006) whereas these effects remained much more discrete or inexistent for dietary supplies within nutritional ranges (Meunier-Salaun et al, 1991). For instance Koopmans et al (2005Koopmans et al ( , 2006 showed that pigs submitted to a social stress had lower plasma cortisol and noradrenaline concentrations when they were fed a large supply of tryptophan.…”
Section: Tryptophan and The Control Of Stress Responsementioning
confidence: 95%
“…Meunier-Salaun et al (1991) have shown that brain serotonin in piglets is linearly related to dietary tryptophan level. A recent study by Koopmans et al (2006) demonstrated supplemental dietary tryptophan increased hypothalamic serotonergic activity of weanling pigs.…”
Section: Dietary Nutrient Level and Balancementioning
confidence: 99%